Stylistic structures in Lama Zuhair ibn Abi Solma (Peace be upon Salma) (Journal of Hama University, 2019)
This research is concerned with looking at the poem "Salih al-Solma for Salma" by Zuhair ibn Abi Solma in an attempt to uncover the structures in which the poet modified his salary to enrich the poetry of the text. He began by studying the semantic level, between the effect of the graphic image in the characterization of poeticism on the poem, The rhythmic level of the internal and external dimension, he tried to reveal the role of rhythm in enriching the meaning on the one hand, and his role in music on the other, and then deliberately to the level of synthesis and chose some syntactic structures in which the poet modified the strict grammatical system, try to show the purpose of the poet of his reliance To these structures, then Khet Searc results of ou findings Semantic, metaphorical, rhythmic, weight, syntactic